French Banks Amid the Global Financial Crisis - Xiao, Yingbin (IMF Working Papers; Working Paper ;, 2009)
This paper runs the gamut of qualitative and quantitative analyses to examine the performance of French banks during 2006-2008 and the financial support measures taken by the French government. French banks were not immune but proved relatively resilient to the global financial crisis reflecting their business and supervision features. An event study of the impact of government measures on CDS, debt, and equity markets points to the reduction of credit risk and financing cost as well as the redistribution of resources. With the crisis still unfolding, uncertainties remain and challenges lie ahead, calling for continued vigilance and enhanced risk management.